Anionic Lipids: A Pipeline Connecting Key Players of Plant Cell Division - Caillaud, Marie-Cécile (Frontiers in Plant Science, 2019)
How cells position their division plane is a critical component of cell division. Indeed, it defines whether the two daughter cells divide symmetrically (with an equal volume) or not and as such is critical for cell differentiation and lineage specification across eukaryotes. However, oriented cell divisions are of special significance for walled organisms such as plants, because cells are embedded and cannot relocate. Correctly positioning the division plane is therefore of paramount important in plants as it controls both asymmetric cell division, but also tissue morphogenesis and organ integrity. While cytokinesis is executed in radically different manners in animals and plants, they both rely on the dynamic interplay between cytoskeleton and membrane trafficking to precisely deliver molecular components to the future site of cell division. It is emerging that, in non-plant organisms, strict regulation of the levels and distribution of anionic lipids―which are minor components of the membrane lipids―is required for successful cytokinesis. This review focus on the recent evidence pointing out the role of this signaling lipids in plant cell division.